Selymatra: A web application for protein‐profiling analysis of mass spectra. (20th September 2021) - Nardone, Davide; Ciaramella, Angelo; Cerreta, Mariangela; Pulcrano, Salvatore; Bellenchi, Gian C.; Leone, Linda; Manco, Giuseppe; Febbraio, Ferdinando
Abstract: Surface enhanced laser desorption/ionization‐time of flight (SELDI‐TOF) mass spectrometry is a variant of the matrix‐assisted laser desorption/ionization‐time of flight (MALDI‐TOF) mass spectrometry. It is used in many cases especially for the analysis of protein profiling and for preliminary screening of biomarkers in complex samples. Unfortunately, these analyses are time consuming and protein identification is generally strictly limited. SELDI‐TOF analysis of mass spectra (SELYMATRA) is a web application (WA) developed to reduce these limitations by (i) automating the identification processes and (ii) introducing the possibility to predict proteins in complex mixtures from cells and tissues. The WA architectural pattern is the model‐view‐controller, commonly used in software development. The WA compares the mass value between two mass spectra (sample vs. control) to extract differences, and, according to the set parameters, it queries a local database to predict most likely proteins based on their masses and different expression amplification. The WA was validated in a cellular model overexpressing a tagged NURR1 receptor, being able to recognize the tagged protein in the profiling of transformed cells. A help page, including a description of parameters for WA use, is available on the website. Abstract : SELYMATRA is a user‐friendly web application for the analysis of SELDI‐TOF MS data, enabling fast and automated protein identification even in complex samples.